Secular Trends in the Incidence of and Mortality Due to Alzheimer’s Disease and Other Forms of Dementia in China From 1990 to 2019: An Age-Period-Cohort Study and Joinpoint Analysis - Gao, Yongliang; Liu, Xiaonan (Frontiers in Aging Neuroscience, 2021)
Background The number of individuals with dementia is increasing, which negatively affects families, communities, and health care systems worldwide. The changes in the incidence of and mortality due to Alzheimer’s disease and other forms of dementia at the national level in China have remained unknown over the past three decades. Methods Following the general analytical strategy used in the Global Burden of Disease Study (GBD) 2019, the age- and sex-specific incidence and mortality rates for dementia in China were analyzed. Trends in the incidence of and mortality due to dementia from 1990 to 2019 were assessed by joinpoint regression analysis. The effects of age, period and cohort on the incidence of and mortality due to dementia were estimated by an age-period-cohort model. Results The age-standardized incidence and mortality rates per 100,000 population were 103.83 (95% UI, 87.93–118.87) and 23.32 (95% UI, 5.66–61.31), respectively, for dementia in 2019. From 1990 to 2019, a significant average annual percentage change (AAPC) in the age-standardized incidence rate was observed in both males [0.49% (95% CI, 0.43–0.55%)] and females [0.31% (95% CI, 0.24–0.38%)], and the age-standardized mortality rate significantly increased in males [0.42% (95% CI, 0.31–0.53%)]. The population aged 55–59 years had the highest AAPC in the incidence of dementia [0.87% (95% CI, 0.81–0.93%)]. The age effect showed that the relative risks (RRs) of incident dementia and dementia-associated mortality increased with age among males and females, and individuals aged 60 years and older had significantly higher RRs. The RR of incident dementia increased with time, and the RR started to substantially increase in 2009. The cohort effect showed that the incidence decreased in successive birth cohorts. Conclusion Alzheimer’s disease and other forms of dementia continue to become more common among males and females in China, and the associated mortality rate in males significantly increased from 1990 to 2019. Early interventions should be implemented to reduce the burden of dementia on individuals at high risk in China.